Lycopene, Mesoporous Silica Nanoparticles and Their Association: A Possible Alternative against Vulvovaginal Candidiasis? - Carvalho, Gabriela Corrêa [UNESP]; Marena, Gabriel Davi [UNESP]; Leonardi, Gabriela Ricci; Sábio, Rafael Miguel [UNESP]; Corrêa, Ione [UNESP]; Chorilli, Marlus [UNESP]; Bauab, Tais Maria [UNESP] (MDPI, 2022)
Commonly found colonizing the human microbiota, Candida albicans is a microorganism known for its ability to cause infections, mainly in the vulvovaginal region known as vulvovaginal candidiasis (VVC). This pathology is, in fact, one of the main C. albicans clinical manifestations, changing from a colonizer to a pathogen. The increase in VVC cases and limited antifungal therapy make C. albicans an increasingly frequent risk in women’s lives, especially in immunocompromised patients, pregnant women and the elderly. Therefore, it is necessary to develop new therapeutic options, especially those involving natural products associated with nanotechnology, such as lycopene and mesoporous silica nanoparticles. From this perspective, this study sought to assess whether lycopene, mesoporous silica nanoparticles and their combination would be an attractive product for the treatment of this serious disease through microbiological in vitro tests and acute toxicity tests in an alternative in vivo model of Galleria mellonella. Although they did not show desirable antifungal activity for VVC therapy, the present study strongly encourages the use of mesoporous silica nanoparticles impregnated with lycopene for the treatment of other human pathologies, since the products evaluated here did not show toxicity in the in vivo test performed, being therefore, a topic to be further explored.
Keywords: antifungal activity; carotenoid; Galleria mellonella; lycopene; mesoporous silica nanoparticles; natural products